Stability-Indicating RP-HPLC Method for Assay of Silver Lactate - V. Srinivasan; H. Sivaramakrishnan; B. Karthikeyan (E-Journal of Chemistry)
A simple, economic and time-efficient stability-indicating, reverse-phase high-performance liquid chromatographic (RP-HPLC) method has been developed for analysis of silver lactate in the presence of degradation products generated by decomposition. When silver lactate was subjected to acid hydrolysis, base hydrolysis, oxidative, photolytic, humidity and thermal stress, degradation was observed during base hydrolysis, oxidation, humidity and thermal stress. The drug was found to be stable to other stress conditions. Successful chromatographic condition of the drug from the degradation products formed under stress conditions was achieved on a phenomenex Gemini column with potassium dihydrogen phosphate buffer, pH adjusted to 2.2 with orthophosphoric acid, as mobile phase. The method was validated for linearity, precision, specificity and robustness and can be used for quality-control during manufacture and assessment of the stability of samples of silver lactate. To the best of our knowledge, a validated stability-indicating LC assay method for silver lactate based on lactic acid is reported for the first time.